Nepal : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2003)
Nepal's public debt-to-GDP ratio is set to decline from 68 percent of GDP at end-2002-03 over the medium term. The 2003-04 budget makes a start in implementing the medium-term fiscal strategy. Government spending will be redirected to social sectors, for poverty alleviation, and be better prioritized. Monetary policy would remain geared to supporting the exchange rate peg to the Indian rupee. Further steps are envisaged to strengthen the Nepal Rastra Bank (NRB), improve the banking environment, and restructure commercial and development banks.